Goalkeeper - specific training for youngsters. Characterization of the importance and structure in the formation process of handball goalkeeper - Castro, J.; Sequeira, P.; Cruz, C. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The study aims to characterize the training of the Handball Goalkepper, identifying the purpose of the exercises performed and the structure of training for atheletes between 11 and 18 years in 24 training sessions.The exercises were considered in the study according to their objective, and the Goalkeeper specific exercises for developed components, moment of occurrence and mode of organization, and classified under the validation of 6 specialists.